Answer:
Step-by-step explanation:
The answers should be 1D, 2C, 3B, 4A, and 5A.
Answer:
- h(x) = -2x^2 -x +3
- Reservoir A releases the same amount of water as Reservoir B over 1 week
Step-by-step explanation:
<u>Given</u>:
f(x) = x^2 -7x +5
g(x) = 3x^2 -6x +2
h(x) = f(x) -g(x)
<u>Find</u>:
h(x)
h(1)
<u>Solution</u>:
The expression for h(x) is found by evaluating its definition:
h(x) = (x^2 -7x +5) -(3x^2 -6x +2)
h(x) = x^2(1 -3) +x(-7 -(-6)) +(5 -2)
h(x) = -2x^2 -x +3
Then h(1) is found by substituting 1 for x:
h(1) = -2(1^2) -(1) +3 = -2 -1 +3
h(1) = 0 . . . . difference in release amounts after 1 week is 0
The true statements are ...
- h(x) = -2x^2 -x +3
- Reservoir A releases the same amount of water as Reservoir B over 1 week
Answer:
1. is 45/2
2. is 12/5
3. is 4/5
4. is 14
5. is 28
6. is 6 hope this helps :)
Step-by-step explanation:
Answer:
![y=-\frac{\sqrt{2}\sqrt{x} }{2} \\y=\frac{\sqrt{2}\sqrt{x} }{2}](https://tex.z-dn.net/?f=y%3D-%5Cfrac%7B%5Csqrt%7B2%7D%5Csqrt%7Bx%7D%20%20%7D%7B2%7D%20%5C%5Cy%3D%5Cfrac%7B%5Csqrt%7B2%7D%5Csqrt%7Bx%7D%20%20%7D%7B2%7D)
Step-by-step explanation: